“Rhetorical Theory of the art of expression” in dealing with new linguistics: "نظرية فنّ البیان البلاغية" في التعاطي مع اللسانيات الجدیدة - خاقاني أصفهاني, محمد (Thi Qar Arts Journal, 2024)
Arabic rhetoric grew up in the embrace of the Holy Qur’an, and the greatest concern of its pioneers was to reveal the aesthetic secrets of this eternal miracle. There is no doubt that it provided great services at that time in highlighting the literary and rhetorical subtleties of the Holy Qur’an, but it gradually froze and calcified, until it overcame on the verge of death, it was deleted from the literary system Western studies, under the pretext that their effectiveness has expired and are no longer suitable for analyzing literary texts in the current era. And they are right, in the opinion of this researcher, because international literature has been exposed to violent trends and has experimented with new types of literary genres that traditional Arabic rhetoric is not suitable for understanding, let alone interpreting and analyzing. This is what prompted the researcher to draw up a new rhetorical system that was officially registered in Iran under the title: “The Theory of the Art of Rhetorical Statement.” It is a theory that has origins (to build it on universal philosophical foundations), rules (to rebuild it by employing modern literary developments), and chapters (to replace the trilogy of meanings, statement, and creativity in Sakaki system). This research is responsible for identifying the seven rules that the researcher believes will guarantee this new system its creativity and modernity to keep pace with what is new in the arenas of literary text in today’s world. The researcher applied the descriptive, analytical, exploratory method to draw the seven chosen rules in his rhetorical theory, which are: areas, positions, paths, spaces, sections, appearances, and levels. It is capable of dealing with rhetoric with new linguistics and literary sciences, which contemporary Western writers considered alternatives to the traditional subject of rhetoric. The research reached results, the most important of which are: the necessity of rebuilding rhetoric by sorting between the areas of pronunciation and meaning, and the positions of the sender and the recipient, introducing the paths of literature and their new spaces, the passages of speech, its oral and written manifestations, and its two levels, the apparent and the hidden, in the rhetorical lesson.